PEMANFAATAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN MINATBELAJAR BAHASA ARAB SISWA KELAS VII MADRASAH TSANAWIYAH MUHAMMADIYAH LIMBUNG - Nasruni Nasruni (Universitas Muhammadiyah Makassar, 2017)
This study aims to determine the utilization of audio visual media in improving interest in learning Arabic language as well as to determine the inhibiting factors in the application of audio visual media utilization media in the seventh grade students of Madrasah Tsanawiyah Muhammadiyah Limbung. The methods used in order to collect data related to the problem were interview, observation, documentation and questionnaire. The population amount 79 with 27 samples taken by way of purposive sampling. The results of this study indicated that the utilization of audio visual media in improving interest in learning Arab language VII grade students MTs. Muhammadiyah Limbung Kec. Bajeng Kab. Gowa as follows: (1) Audio-visual media had a very important role in learning Arabic language of students, because audio visual media in accordance with the character of MTs students. It was more interesting if learning was explained by hearing and sight. (2) Inhibiting factors in the use of audio visual media on learning Arabic language students VII MTs. Muhammadiyah Limbung was Lack of facilities and infrastructure such as computers and LCDs provided by schools so that in the application of the image media, teachers had to draw manually related images to be displayed in accordance with the teaching materials or subject matter that would be explained. Keywords: Audio Visual Media, Interests, Arabic